1983
DOI: 10.1002/jobm.19830230915
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological implications of electric field effects VII. Stimulation of plasmid transformation of Bacillus cereus protoplasts by electric field pulses

Abstract: The aim of this study was to check the action of electric field pulses (1) on the survival of intact cells and protoplasts of Bacillus cereus and ( 2 ) on the transformation frequency of these protoplasts with plasmid DNA from Bacillus thuringiensis transformants. -B. cerew cells and protoplasts are very resistant to high electric field pulses in the microsecond range. The transformation frequency of B. cereus protoplasts with plasmids from B. thuringiensis (PUB 110) can be increased by about one order of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Electroporation based on high electrical field pulses to facilitate entrance of exogenous materials into cells (Neumann and Rosenheck 1972;Zimmermann et al 1973) was initially used to introduce foreign genes into mammalian cells (Neumann et al 1982), plant protoplasts (Fromm et al 1985;Ou-Lee et al 1986), and yeast (Hashimoto et al 1985;Karube et al 1985). In contrast and perhaps as traditional transformation of Escherichia coli is efficient (107-108 transformants/~g DNA) (Hanahan 1983), bacteriologists have only more recently become interested in transformation mediated by electroporation, although it was shown to be effective with protoplasts of Bacillus cereus as early as 1983 (Shivarova et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Electroporation based on high electrical field pulses to facilitate entrance of exogenous materials into cells (Neumann and Rosenheck 1972;Zimmermann et al 1973) was initially used to introduce foreign genes into mammalian cells (Neumann et al 1982), plant protoplasts (Fromm et al 1985;Ou-Lee et al 1986), and yeast (Hashimoto et al 1985;Karube et al 1985). In contrast and perhaps as traditional transformation of Escherichia coli is efficient (107-108 transformants/~g DNA) (Hanahan 1983), bacteriologists have only more recently become interested in transformation mediated by electroporation, although it was shown to be effective with protoplasts of Bacillus cereus as early as 1983 (Shivarova et al 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The first report on electroporation-based gene transfer was published in 1982 [41], but it was achieved on mammalian cells (which lack a wall) and moreover not heritable, while in organisms with a wall the initial experiments performed in 1983 suggested this to be achievable only after its complete removal [42]. This misapprehension was, however, due to insufficient amplitude of the applied electric pulses, and development of stronger pulse generators quickly led to transformation of microorganisms with an intact wall: yeasts in 1985 [43], bacteria in 1987 [44], and archaea and microalgae in 1991 [45,46].…”
Section: Electrotransformationmentioning
confidence: 98%
“…Shivarova et al (1983) used total plasmid DNA from B. thuringiensis subsp. Shivarova et al (1983) used total plasmid DNA from B. thuringiensis subsp.…”
Section: B Gram-positive Bacteriamentioning
confidence: 99%
“…Although largely unnoticed, Shivarova et al ( 1983) reported the transformation of protoplasts of Bacillus cereus; by electroporation. Chapter 13 describes the applications of electroporation to eukaryotic cells.…”
mentioning
confidence: 99%